Analysis of patterns of urban sprawl and surface urban heat island in solan town of himachal pradesh using remote sensing and gis. Issue 1 (1st February 2023) - Mehta, T; Ghoshal, S; Mahajan, Y; Sharma, M; Neha, K
Abstract: Rapid unplanned urbanization consequently influencing the land surface temperature globally that lead to Urban Heat Island (UHI) phenomenon that has negative impact on the quality of life of population exist within that area. Impervious surfaces effect the functioning of ecosystem that's why urban monitoring is important. Present study was focused on detection of presence of the UHI phenomenon in the Solan town of Himachal Pradesh (H.P.) from year 1990, 2000, 2010 and 2020. Multitemporal analysis is performed to analyze trend of temperature using Landsat 5, 7 and 8 thermal infrared sensors processed within Geographical Information System (GIS). Google Earth engine also used as a platform for the detection of urban sprawl with the help of classified map extracted from it. R software used for the detection of fragmentation and other landscape indices on the classified map. Region of interests (ROIs) was created in the urban and surrounding rural area to analyze the difference in temperature and landscape metrics in both of ROIs. Study highlighted the presence of Surface Urban Heat Island (SUHI) phenomenon in the medium size town of Solan in all the decades with the maximum LST difference of 1.92°C in year 1990, 0.68°C in year 2000, 1.02°C in year 2010 and 2.12°C in year 2020 between the two ROIs. Temperature values in year 2020 has declined due to reforestation in the area and the consequence of global pandemic lead to change in temperature due to lower pollutant concentration. LST variation indicate a rise of 4.61°C in the minimum and 9.19°C in the maximum temperature from 1990 to 2010. Urban sprawl has been reported, the urban expansion was maximum from year 1990 to 2000 in the Centre of city with the percentage of 31.27 km 2 while total rate of change in urban surfaces is 131.48km 2 which includes rural area along with road has been converted in impervious surface with the passage of years. Overall accuracy of the classified maps was 88%. The classified maps indicate correlation of landscape indices with the urban expansion of town where heterogeneity significantly increased with time whereas patch number and density is increasing with the urban growth and declining with reforestation in the urban and rural ROIs it fluctuate accordingly. This study reported the need of effective and sustainable urban planning method in the developing cities of Himalayas. Policy makers should introduce green spaces and plantation in urban area to mitigate the UHI phenomenon in future.